2000
DOI: 10.1002/1096-9098(200005)74:1<21::aid-jso5>3.3.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Total mesorectal excision for surgical treatment of rectal cancer

Abstract: Background and Objectives:The aim of our study was to retrospectively evaluate the results of 2 groups of patients admitted and treated for rectal cancer. Methods: One hundred and fifty-one patients were available for evaluation. Eighty (group A) were radically operated with the standard technique; 71 (group B) underwent total mesorectal excision (TME). Groups were similar according to demographics, staging, and pathological data. Mean follow-up was 73.5 months. Results: No operative mortality was observed. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…Bolognese et al . compared results in a single Italian hospital before and after TME and concluded that higher incidence of postoperative anastomotic leak is offset by reduced incidence of cancer‐related 5‐year mortality (from 62% to 20%) after TME [48]. Garcia‐Granero et al .…”
Section: Resultsmentioning
confidence: 99%
“…Bolognese et al . compared results in a single Italian hospital before and after TME and concluded that higher incidence of postoperative anastomotic leak is offset by reduced incidence of cancer‐related 5‐year mortality (from 62% to 20%) after TME [48]. Garcia‐Granero et al .…”
Section: Resultsmentioning
confidence: 99%
“…Uncontrollable massive bleeding often happened. We must pay attention to the high mortality rate after CVS, as reported by Bolognese [36]. Overall LLA seems to be as safe as THE for most rectal cancer patients, at least for Japanese patients.…”
Section: Discussionmentioning
confidence: 99%
“…The 5‐year survival is reported to be 50% [22]. Recurrence rates reported by different groups vary widely, from 4 to 40% at 5 years [23–25]. At the time of writing, the follow‐up period of our study had not reached a minimum of 5 years for all patients and therefore we were unable to express strong views on the long‐term survival benefits of our protocols; however, this was not the aim of the current study.…”
Section: Discussionmentioning
confidence: 92%